Systematic Literature Review: Peran Kepemimpinan Berbasis Pancasila Dalam Membangun Organisasi Yang Berdaya Saing - Fiha Fauzia; Usiono Usiono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research focuses on the role of leadership rooted in Pancasila values in shaping competitive organizations. The research methodology employs SLR to assess literature related to this concept. The steps of SLR, starting from formulating research problems, developing review protocols, searching for literature, screening inclusions, assessing literature quality, to reporting findings, are detailed. The research findings highlight various aspects of leadership, the leader's role in organizational transformation, leadership styles, Pancasila values, and the concept of competitiveness within organizations.